Determination of the 144Ce/238U atomic ratio in spent nuclear fuel using double spike isotope dilution mass spectrometry. Issue 6 (10th May 2022) - Beaumais, Aurélien; Nonell, Anthony; Caussignac, Céline; Mialle, Sébastien; Stadelmann, Guillaume; Janin, Myriam; Isnard, Hélène; Aubert, Michel; Vercouter, Thomas; Chartier, Frédéric
Abstract : Determination of the 144 Ce/ 238 U ratio in spent nuclear fuels using the double isotope dilution technique associated with thermal ionization mass spectrometry measurements. Abstract : The low abundance cerium-144 radionuclide is one of the significant contributors to the decay heat from spent nuclear fuel for cooling times of less than ten years after nuclear reactor discharge. The accurate quantification of the 144 Ce content (or 144 Ce/ 238 U) in irradiated nuclear fuel is necessary to validate and extend the neutronic calculation codes as well as to improve the short-term nuclear waste management strategies. In order to quantify the 144 Ce/ 238 U atomic ratios at low uncertainty, we developed a new analytical technique based on double spike isotope dilution associated with mass spectrometry. This includes (1) the chemical elimination of the major neodymium-144 isobaric interference by two steps of liquid chromatography prior to isotope analysis by Thermal Ionization Mass Spectrometry (TIMS) using both total evaporation and sequential methods, and (2) the preparation and use of an in-house double spike solution, using a mixture of a natural Ce solution with a 233 U-enriched solution. This new approach was applied for the first time on two Mixed Oxide (MOx) spent nuclear fuel samples and allowed the determination of 144 Ce/ 238 U atomic ratios ranging from 35 × 10 −6 to 59 × 10 −6 with a relative expanded uncertainty of measurement of around 1% at a 95% confidence level.